2007
DOI: 10.1088/0957-0233/18/8/047
|View full text |Cite
|
Sign up to set email alerts
|

Power transistor near-infrared microthermography using an intensified CCD camera and frame integration

Abstract: In this work, a high performance near-infrared thermal microscope designed to characterize the thermal behaviour of a power metal–oxide–silicon field-effect transistor (MOSFET) is presented. This non-destructive method is based on the measurement of the thermal radiation emitted by the power transistor in the spectral domain close to 800 nm using an intensified CCD camera. Although the intensifier unit is developed specially for low-level radiant applications, an image processing technique based on lock-in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…The fact that bodies at temperatures above 500 C certainly emit electromagnetic radiation wavelengths in the 0.8 lm to 1.2 lm range, which can be detected by CCD devices [3,27,28] affords CCD N-IR measurements. For example a similar technique used by Dhokkar et al [29] has been used in order to study transistor technology temperature fields in the micro scale. While a measurement as in Ref.…”
Section: N-ir Technology For Sofc Studymentioning
confidence: 99%
“…The fact that bodies at temperatures above 500 C certainly emit electromagnetic radiation wavelengths in the 0.8 lm to 1.2 lm range, which can be detected by CCD devices [3,27,28] affords CCD N-IR measurements. For example a similar technique used by Dhokkar et al [29] has been used in order to study transistor technology temperature fields in the micro scale. While a measurement as in Ref.…”
Section: N-ir Technology For Sofc Studymentioning
confidence: 99%
“…Yang et al [7], Wu et al [8] and Carbillet et al [9] performed research on the principle of how the electron-multiplying chargecoupled device camera greatly enhanced the contrast of the acquired images. Frame-accumulation algorithm [10,11] is also widely used for LLL imaging. Frensch [12] established a system which could improve the impression of a digitized image with a low amplitude resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Dhokkar et al [5] reported a systematic investigation about the use of a high performance near-infrared thermal microscope to evaluate the thermal behavior of a power metal-oxide-siliconfield-effect transistor. IRT images of the power transistor are presented and discussed for several values of the drain current.…”
Section: Introductionmentioning
confidence: 99%